BIMBINGAN BAGI ANAK TUNA CAKAP BELAJAR SD GMIT 33 MORU 1 - Maria Delia B. Tukan; Mahalita S. Moban , Lutgardis S. Maure , Loriana Laupada , Yessy Mata, Petrus Mau Tellu Dony (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
This study aims to explore the guidance methods used by teachers to overcome learning difficulties in communication, reading, writing, arithmetic, and social-emotional challenges at SD GMIT 33 MORU 1. Appropriate guidance is essential to help students develop their academic, social, and emotional potential optimally. The research method used is descriptive qualitative with data collection techniques of in-depth interviews with classroom teachers as key informants. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted in several stages, namely data reduction, data presentation, and conclusion drawing. The results of the study indicate that students at SD GMIT 33 MORU 1 experience difficulties in communication, reading, writing, arithmetic, and social-emotional development during the learning process, prompting teachers to utilise objects in their surroundings as learning media. The difficulties mentioned above are influenced by two factors, namely internal and external factors. Internal factors include mild brain disorders that cause mental and emotional instability in students. External factors include genes, negative experiences in the past, an unsupportive living environment, family pressure, and a lack of support and special attention from parents. In overcoming learning disabilities, teachers use a personalised, empathetic approach between teachers, students, and parents. However, despite this, the results are not yet optimal due to several limitations faced by teachers, such as limited specialised programmes and professional teaching staff. However, the teachers' dedication to education remains unwavering despite these limitations, and they continue to motivate and encourage students when they become bored or reluctant to participate in lessons. Based on the research findings, it is concluded that structured, communicative, and continuous guidance is crucial in helping students with learning disabilities achieve optimal development in line with their needs and abilities.